Pengaruh Karakteristik Wirausaha, Lingkungan Eksternal, Kecanggihan Teknologi dan Strategi Bertahan Terhadap Keberlangsungan UMKM di Kecamatan Gerung, Kabupaten Lombok Barat Selama Pandemi Covid-19: (The Influence of Entrepreneurial Characteristics, External Environment, Technological Sophistication and Defense Strategies on the Sustainability of MSMEs in Gerung District, West Lombok Regency During the Covid-19 Pandemic) - Selpia Wulan Dari; Biana Adha Inapty; Yusli Mariadi (UPT Penerbitan Universitas Jember, 2022)
This study aims to determine the effect of entrepreneurial characteristics, external environment, technological sophistication and survival strategies on the sustainability of MSMEs in Gerung District, West Lombok Regency during the COVID-19 pandemic. This study takes a quantitative approach to associative research. This research relies on original data. All MSMEs in Gerung District, West Lombok Regency, were included in this study. Purposive sampling was employed using a sample of 59 SMEs in this study. Using Partial Least Square (PLS) version 3.0, investigate the impact of entrepreneurial traits, external environment, technological sophistication, and survival strategies on the sustainability of MSMEs. The findings reveal that entrepreneurial traits and technological sophistication have no bearing on MSMEs' long-term viability, however the environment and survival tactics have a favorable and significant impact. Expanding the population and increasing the number of samples, upgrading instruments, and adding pertinent independent variables such as entrepreneurial spirit and risk calculation abilities are all proposals for future research. The implications of this research are expected to be additional information for MSME actors and interests in the business world first during the COVID-19 pandemic.